Neuropathic pain - Colloca, L; Ludman, T; Bouhassira, D; Baron, R; Dickenson, A; Yarnitsky, D; Freeman, R; Truini, A; Attal, N; Finnerup, N; Eccleston, C; Kalso, E; et al. (Nature Publishing Group, 2017)
Neuropathic pain is caused by a lesion or disease of the somatosensory system, including peripheral fibres (Aβ, Aδ and C fibres) and central neurons, and affects 7-10% of the general population. Multiple causes of neuropathic pain have been described and its incidence is likely to increase owing to the ageing global population, increased incidence of diabetes mellitus and improved survival from cancer after chemotherapy. Indeed, imbalances between excitatory and inhibitory somatosensory signalling, alterations in ion channels and variability in the way that pain messages are modulated in the central nervous system all have been implicated in neuropathic pain. The burden of chronic neuropathic pain seems to be related to the complexity of neuropathic symptoms, poor outcomes and difficult treatment decisions. Importantly, quality of life is impaired in patients with neuropathic pain owing to increased drug prescriptions and visits to health care providers, as well as the morbidity from the pain itself and the inciting disease. Despite challenges, progress in the understanding of the pathophysiology of neuropathic pain is spurring the development of new diagnostic procedures and personalized interventions, which emphasize the need for a multidisciplinary approach to the management of neuropathic pain.